Beauty and the beholder: the role of visual sensitivity in visual preference - Spehar, Branka; Wong, Solomn; van de Klundert, Sarah; Lui, Jessie; Clifford, Colin W.; Taylor, Richard (Frontiers in Human Neuroscience, 2015)
For centuries, the essence of aesthetic experience has remained one of the most intriguing mysteries for philosophers, artists, art historians and scientists alike. Recently, views emphasizing the link between aesthetics, perception and brain function have become increasingly prevalent (Zeki, 1999; 2002; 2013; Ishizu & Zeki, 2013; Ramachandran & Hirstein, 1999; Livingstone, 2002). The link between art and the fractal structure of natural images has also been highlighted (Spehar, Newell, Clifford & Taylor, 2003; Graham and Field, 2007; Graham & Redies, 2010). Motivated by these claims and our previous findings that humans display a consistent preference across various fractal images, we explore here the possibility that observers' preference for visual patterns might be related to their sensitivity for such patterns. We measure sensitivity to simple visual patterns (sine-wave gratings varying in spatial frequency and random textures with varying fractal exponent) and find that they are highly correlated with visual preferences exhibited by the same observers. Although we do not attempt to offer a comprehensive neural model of aesthetic experience, we demonstrate a strong relationship between visual sensitivity and preference for simple visual patterns. Broadly speaking, our results support assertions that there is a close relationship between aesthetic experience and the sensory coding of natural stimuli.